Full-Bridge DC-DC Converter with Synchronous Rectification Based on GaN Transistors - Xin Wang; Qingsong Zhao; Zenglong Zhao; Fanyi Meng (Journal of Low Power Electronics and Applications)
This study presents a hard-switching full-bridge DC-DC converter with synchronous rectification based on Gallium Nitride (GaN) transistors to evaluate the advantages of GaN devices in power supplies. In comparison to traditional silicon-based devices, GaN transistors are utilized in both the primary and secondary stages of the converter, exploiting GaN’s lower on-resistance to enhance performance. The converter operates at a switching frequency of 300 kHz, with an input voltage range of 36 V to 75 V, delivering an output of 28 V/42 A. Experimental results show that the GaN-based converter achieves an output power of 1176 W within standard half-brick package dimensions. The measured peak efficiency is 97.1%, and the power density reaches 430 W/in3. These findings demonstrate that GaN-based converters offer superior efficiency and power density compared to conventional silicon-based designs, making them highly suitable for aerospace, automotive, and communication power supplies.